Facial nerve reconstruction for flaccid facial paralysis: a systematic review and meta-analysis - Zumbusch, Friedemann; Schlattmann, Peter; Guntinas-Lichius, Orlando (Frontiers in Surgery, 2024)
Objectives To determine the functional outcome after facial nerve reconstruction surgery in patients with flaccid facial paralysis. Methods A systematic review and meta-analysis was performed on studies reporting outcomes after direct facial nerve suture (DFS), facial nerve interpositional graft suture (FIGS), hypoglossal–facial nerve suture (HFS), masseteric–facial nerve suture (MFS), and cross-face nerve suture (CFS). These studies were identified from PubMed/MEDLINE, Embase, and Web of Science databases. Two independent reviewers performed two-stage screening and data extraction. A favorable result was defined as a final House–Brackmann grade I–III and is presented as a ratio of all patients in percentage. Pooled proportions were calculated using random-effects models. Results From 4,932 screened records, 54 studies with 1,358 patients were included. A favorable result was achieved after DFS in 42.67% of the patients [confidence interval (CI): 26.05%–61.12%], after FIGS in 66.43% (CI: 55.99%–75.47%), after HFS in 63.89% (95% CI: 54.83%–72.05%), after MFS in 63.11% (CI: 38.53%–82.37%), and after CFS in 46.67% (CI: 24.09%–70.70%). There was no statistically significant difference between the techniques (Q = 6.56, degrees of freedom = 4, p = 0.1611). Conclusions The established facial nerve reconstruction techniques including the single nerve cross-transfer techniques produce satisfactory results in most of the patients with permanent flaccid facial paralysis. An international consensus on standardized outcome measures would improve the comparability of facial reanimation techniques.